Analysing the evolution and patterns of the gig economy: a bibliometric examination of growth and trends - Soumya Vadavi; Jekka Chandrasekaran Sharmiladevi (Cogent Business & Management, 2024)
This article examines global academic research and provides an overview of the gig economy. The article provides a comprehensive framework based on a literature review, offering insights into the evolution of research trends, key themes, and collaborative dynamics within this evolving field. Our study focuses on the gig economy as a broader economic system characterised by short-term contracts, freelance work, and gig employment. This article presents a bibliometric analysis using the VOS Viewer tool; we examined 341 documents from the Scopus database covering January 2016 to March 2024. Our findings reveal a significant increase in the gig economy publication research. We identified three contemporary cluster themes, which include “The Changing Work Environment in the Digital Age,” “Navigating the Contemporary Labour Landscape,” and “Empowering the Future Workforce.” The article offers practical insights into the gig economy, suggests guidelines that will enhance working conditions and the welfare of gig employees and provides valuable implications for researchers, shedding light on the current state and potential future directions of the gig economy.
Keywords: J3; J5; J8; O1; O5; 650; Gig economy; contract employees; bibliometric analysis; labour market; behavioural changes; work-life balance